Peningkatan Penjualan di Market Place Shopee Pada Era Digitalisasi - Khatimah, Betty Nur; Yuliana, Rahmi; Hamdani, Muliawan (EconBank: Journal of Economics and Banking, 2023)
This research aims to determine the influence of online marketing, marketing strategies and digital marketing on increasing sales. The sample in this study was 100 respondents who were permanent product sellers who sold their products on the Shopee marketplace. Multiple Linear Regression Analysis was used to analyze the data in this research. The research results show that online marketing and digital marketing have a positive effect on increasing sales. This means that better management in online marketing and good digital marketing can increase sales in the Shopee market. Meanwhile, marketing strategies were unable to influence increased sales in the Shopee marketplace. This happens because competition in the Shopee marketplace is currently increasingly competitive, so changes in marketing strategies are needed that can attract potential consumers